EVALUATION OF INTERNET AND SOCIAL MEDIA ACCESS AND USAGE AMONG WIC CLIENTS - Sempa, Judith; Sempa, Judith (My University, 2016)
For my field experience, my major project was to assess the use of internet and social media among WIC (women, infants, and children Food and Nutrition Service) clients, receiving services from the Riley County Family and Child Resource Center. To follow this up, I designed a video using Adobe voice, an application on the Apple operating system used for mobile devices. In addition to this project, I was also involved in community outreach field activities undertaken by the Extension office, under Ginny’s supervision.
Keywords: Riley County Extension; EFNEP; Community Outreach; Social Media